PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAHKOTA GORONTALO - Sri Meike Jusup (AkMen JURNAL ILMIAH, 2020)
This study aims to determine and analyze how much influence competence has on employee performance. This research was conducted at the Secretariat of the Regional People's Representative Council (DPRD) Gorontalo City by taking 38 employees as the research sample. Data collection techniques using questionnaires and using multiple regression as a method of data analysis. The results showed that competence simultaneously affects employee performance by 60.2% and 39.8% is influenced by external variables that are not studied. Knowledge (X1) of 37.0%, Skills (X2) of 32.6%, Traits / traits (X3) of 52.3%, Motive (X4) of 72.0%, Self-concept (X5) of 142 , 0%, partially affects Employee Performance (Y).